Laser Ablation Generation of Antimony Selenide Clusters: Laser Desorption Ionization (LDI) Quadrupole Ion Trap Time of Flight Mass Spectrometry - Huang, Fei; Prokeš, Lubomír; Havel, Josef (Journal of the American Society for Mass Spectrometry, 2019)
The binary system Sb-Se was studied via laser ablation using antimony-selenium mixtures made from powdered elements in various ratios generating new SbmSen clusters. The results show that in addition to Sbm+ (m = 1-8) and Sen+ (n = 2-9) clusters, a series of SbmSen+ clusters such as SbSe1-8+, Sb2Se1-6+, Sb3Se1-5+, Sb4Se1-3+, and Sb5Se1,2+ is generated. In addition, some low intensity oxidized clusters like Se6O2+, Se7O2+, and SbSe2-6O5+ and partially hydroxylated clusters (SbSeO2H7+, SbSe5O4H+) are also formed. In total, 24 new antimony selenide clusters were generated. The knowledge gained can contribute to the elucidation of the structure of SbmSen glasses. Graphical Abstract.
Keywords: Antimony selenides; Laser ablation; Laser desorption ionization; Clusters; Chalcogenide glasses; Quadrupole ion trap mass spectrometry